Maxillofacial Fractures due to Falls: does Fall Modality Determine the Pattern of Injury? - Fabio Roccia; Paolo Boffano; Francesca A. Bianchi; Emanuele Zavattero (eJournal of Oral Maxillofacial Research, 2014)
Objectives: In several epidemiological studies of maxillofacial trauma, falls were one of the most frequent causes of facial injury. The aim of this study is to analyse the patterns of fall-related maxillofacial injuries based on the height of the fall.